Conceptual Analysis of Educational Management Information Systems for Optimizing the Learning Process - Masruri, Muhammad Naf’an (CV. Megantara Abdi Nusa, 2025)
This study presents a conceptual analysis of Educational Management Information Systems (EMIS) and their role in optimizing the learning process. Using a qualitative literature review approach, the research synthesizes relevant national and international journal articles, conference proceedings, books, and official documents published within the last ten years. The findings reveal that EMIS plays a strategic role in integrating academic, administrative, infrastructural, and human resource data to support effective, data-driven decision-making. Beyond its administrative functions, EMIS serves as an analytical tool for enhancing the quality of teaching and learning through accurate, timely, and relevant information management. However, its implementation faces several challenges, including technological infrastructure limitations, uneven human resource competencies, budget constraints, and resistance to change. Strategies for overcoming these challenges include phased implementation, intensive user training, policy support, and integration with complementary technologies such as Learning Management Systems (LMS). This study highlights the importance of conceptual mapping of EMIS models to align development with the evolving needs of the education sector in the digital era.